Advanced numerical simulation methods from CAD data directly to simulation results - Beer, G. (Gernot) (CRC Press/Balkema, 2015)
This book is an entertaining, easy to read introduction to advanced numerical modeling. The aim of the book is to lead the reader on a journey towards the 'holy grail' of numerical simulation, namely one without the requirement of mesh generation, that takes data directly from CAD programs. On this journey readers will discover the beauty of Non-uniform Rational B-Splines or NURBS and see how well they are suited for describing geometry, discover how CAD programs work and how their data can be used for simulation